PENGARUH SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA PT. SINAR KALIMANTAN BERAU TANJUNG REDEB - Indriani, Ira (STIE Muhammadiyah Tanjung Redeb, 2018)
The purpose of research conducted is to find out how big the influence of distribution channels on sales volume at PT. Sinar Kalimantan Berau Tanjung Redeb. Analyzer used in this research is simple linear regression equation. The result of research that has been done, can be seen that simple linear regression equation about distribution channel to sales volume at PT. The Berau Kalimantan ray is Y = - 7254.487.642,28 + 124.071.508.09 X, this result shows a positive influence. Where each addition of 1 distribution channel will affect the panjualan volume of Rp. 124.071.508.09. Correlation coefficient from result of distribution channel analysis to sales volume there is strong correlation that is equal to 64%, where increasing of distribution channel will be followed by increase of sales volume. The value of coefficient of determination indicates that the ups and downs of sales volume at PT. Sinar Kalimantan Berau is influenced by distribution channels by 41%, while the rest is influenced by other variables by 59%. Hypothesis testing that has been proposed before, that is whether distribution channel have significant effect to sales volume at PT. Sinar Kalimantan Berau, then t test with degrees of freedom df (degree of freedom) = n-2, 21-2 = 19 is 3.65 with ttable value 2.093. Then the value of t arithmetic (th) compared with the value (tt), with the result of th greater than tt (th> tt), then the hypothesis proposed in this study accepted or proved that the distribution channel significantly influence the sales volume at PT. Sinar Kalimantan Berau